A LONGITUDINAL ANALYSIS ON INTELLECTUAL STRUCTURE OF HUMAN RESOURCES MANAGEMENT: THEORETICAL FOUNDATIONS AND RESEARCH TRENDS - Mehmet Bağış; Liridon Kryezıu; Kadir Ardıç; Ensar Selman Karagüzel (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
In thisstudy, the intellectual structure of the field of human resources management(HRM) has been investigated and new theoretical foundations and research trendsthat will contribute to the development of the field have been proposed.Content analysis was used in the research and a longitudinal analysis wasperformed. The results show that sociology-based organizational theories furtheraffected the field in the 1990s. In the 2000s, it was determined that thedominant theories in the field were human capital theory from economydiscipline, social exchange theory from sociology discipline, and resourcebased view from strategic management discipline. In the 2010s, human capitaltheory from economy discipline, social capital theory from sociologydiscipline, and resource based view from strategic management discipline hadwidespread effects in the field. Finally, strategic human resource management(SHRM), outcomes and human resources practices were determined as the researchtrends that have been most effective on the field from the 1990s to thepresent. However, the context research trend was less effective in the fieldcompared to other research trends. As a result, it can be stated that future researchesthat want to contribute to the field of human resources management can benefitfrom theory of the growth of the firm, Austrian school of economics, strategyas a practice and new institutional economies. In addition, research trends in the future of thefield could be stated as the effects of industry 4.0, e-HRM, and artificialintelligence studies on human resource management.